2006
DOI: 10.1139/s05-041
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of UV irradiation on eight species of Bacillus

Abstract: Ultraviolet irradiation has commonly been used in the indoor environment to eliminate or control infectious diseases such as tuberculosis in medical care facilities. Heating, ventilating, and air-conditioning (HVAC) system components such as duct-liners, cooling coils, drip-pans, interior insulation, and areas subjected to high levels of moisture can create an environment that is prone to biological contamination. Air supplied to indoor environments can carry biological contaminants that can expose numerous bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 9 publications
0
18
1
Order By: Relevance
“…For example, Kowalski (2009) Menetrez et al (2006) reported D 90 values of greater than 175 J/m 2 for spores irradiated while resting on agar plates which is higher than our reported values. Menetrez used B. subtilus var.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…For example, Kowalski (2009) Menetrez et al (2006) reported D 90 values of greater than 175 J/m 2 for spores irradiated while resting on agar plates which is higher than our reported values. Menetrez used B. subtilus var.…”
Section: Discussioncontrasting
confidence: 79%
“…Recent laboratory studies evaluating the kill effect of UV-C were conducted with single spores or close to single spore sizes on surfaces and in the air (Miller and Macher 2000;Ko et al 2002;Lin and Li 2002;Xu et al 2005;Foarde et al 2006;Menetrez 2006;Coohill and Sagripanti 2009;King et al 2011). However, by neglecting multispore clusters, little is known about the decay of potentially equally hazardous larger clusters such as those belonging to aerosols released by sneezing and coughing and other aerosols generated by crude or sophisticated methods.…”
Section: Introductionmentioning
confidence: 99%
“…anthracis stern.) exposed to UVGI irradiation (Menetrez et al, 2006(Menetrez et al, , 2008b. Most of these microorganisms have been identifi ed as being present in HVAC air-handling units (Levetin et al, 2001) and responsible for the transmission of airborne disease (Brickner et al, 2003).…”
Section: Uvc Irradiationmentioning
confidence: 99%
“…With distance and irradiance constant, time of exposure is the controlling variable. The percent kill and k value for each organism were calculated for various periods of exposure (Menetrez et al, 2006(Menetrez et al, , 2008b.…”
Section: Uvc Irradiationmentioning
confidence: 99%
See 1 more Smart Citation